The relationship between the speed of motor reaction and short-distance-runs and the effectiveness of play in defense and offense in basketball - Hucinski, T.; Lapszo, J.; Tymanski, R.; Zienkiewicz, P. (Kinesiology, 2007)
In this paper a study of basketball players` psychomotor efficiency is presented. The psychomotor efficiency was tested in a simulated play in defence, which permitted the measurement of the speed of anticipatory and orientation reacting, as well as anticipatory ability. The movement efficiency was measured by timing the 5, 10, and 30 m runs. The relationships between the tested factors and effectiveness of play in offense and defence were examined. Nineteen highly skilled basketball players of an average age of 15.3 years participated in the study. It was found that the tested psychomotor efficiency factors correlated with the effectiveness of actual play in defence. The study has also shown that the speed of short distance runs (5, 10, 30 m sprint) plays an important role in offense. The following coefficients were obtained: correlation between the effectiveness of play in defence and the speed of anticipatory reacting (0.48), anticipation (-0.50), the index of psychomotor efficiency (-0.53) and between the effectiveness in offense and times of 5 m (0.39), 10 m (0.46) and 30 m (0.47) runs.